IMPLEMENTASI PENGUATAN PROFIL PELAJAR PANCASILA (P5) OLEH MAHASISWA KKN INAIS GUNA MENINGKATKAN KUALITAS PENDIDIKAN DI DESA BANYUWANGI KECAMATAN CIGUDEG KABUPATEN BOGOR - Lestari, Hana; Rahmawati, Ima; Jamil, Muhamad; Amaliyah, Pirda; Hasanah, Siti Lutfiatul (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
P5 Extension (Strengthening Pancasila Student Profile Project) is a program that aims to increase understanding and implementation of the Pancasila student profile in the school environment. This activity was carried out by INAIS KKN students in collaboration with all teachers in Banyuwangi Village, Cigudeg District, Bogor Regency. The main resource person in this activity was Dr. Hana Lestari, M.Pd, an expert in the field of education. The aim of this outreach is to provide teachers with an in-depth understanding of the P5 concept and how to integrate it into the school curriculum. The results of this outreach show that teachers have a better understanding of P5 and are ready to apply Pancasila values ​​in the learning process.